2018
DOI: 10.1186/s12998-018-0217-8
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence for spinal X-ray use in the chiropractic profession: a narrative review

Abstract: The use of routine spinal X-rays within chiropractic has a contentious history. Elements of the profession advocate for the need for routine spinal X-rays to improve patient management, whereas other chiropractors advocate using spinal X-rays only when endorsed by current imaging guidelines. This review aims to summarise the current evidence for the use of spinal X-ray in chiropractic practice, with consideration of the related risks and benefits. Current evidence supports the use of spinal X-rays only in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(132 citation statements)
references
References 114 publications
4
118
0
1
Order By: Relevance
“…In the absence of "red flags", the use of spinal radiographs is not recommended [3][4][5][6][7]. Nevertheless, factions of chiropractors, including the International Chiropractic Association promote the use of routine or repeat radiographs to assess the structure and function of the spine [12][13][14]. This practice which dates back to 1910 was initiated when no evidence was available to guide the judicious use of spine radiographs [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of "red flags", the use of spinal radiographs is not recommended [3][4][5][6][7]. Nevertheless, factions of chiropractors, including the International Chiropractic Association promote the use of routine or repeat radiographs to assess the structure and function of the spine [12][13][14]. This practice which dates back to 1910 was initiated when no evidence was available to guide the judicious use of spine radiographs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Papers in this series have again revealed deeply rooted disagreements within the chiropractic profession about what chiropractic is, and what it should be, as a profession [13,19,20], as well as disagreements and variation in relation to education of chiropractors [14,15] and chiropractic clinical practice [11]. In our opinion, it is ironic that while chiropractic has a strong presence in large parts of the world [3], is taking on increasingly important roles in disability prevention [6,7,17], in the military [5] and in interprofessional care [8] as well as growing research capacity [16], discussions about fundamental values and direction of the profession are unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Axén et al systematically reviewed evidence pertaining to chiropractic maintenance care and concluded that significant advances had been made in recent decades regarding what maintenance care is, when it should be applied, and what outcomes to expect [10]. Jenkins et al reviewed practice guidelines dealing with use of spinal x-ray in chiropractic practice and concluded that routine use of x-ray is not in accordance with current evidence and practice guidelines [11]. Hansen et al reported that chiropractors (at least in Denmark), when surveyed, commonly reported workrelated physical acute or overuse injuries in the low back, wrist, thumb and shoulder, but were very satisfied with their job and had a good psychosocial work environment [12].…”
Section: Commentarymentioning
confidence: 99%
“…This limitation was most pronounced for the topic of diagnostic imaging, where there is still a lack of literature specifically addressing the use of imaging for the purposes of manual care. 82,83 We expect this gap to be increasingly addressed in the future; in fact, an article addressing the topic was published just after we completed the consensus process for this project. 83 Another limitation may be perceived as the composition of our Delphi panel, which was exclusively DCs, although some were cross-trained in other disciplines.…”
Section: Limitationsmentioning
confidence: 99%
“…82,83 We expect this gap to be increasingly addressed in the future; in fact, an article addressing the topic was published just after we completed the consensus process for this project. 83 Another limitation may be perceived as the composition of our Delphi panel, which was exclusively DCs, although some were cross-trained in other disciplines. However, the composition was planned this way because we intended the recommendations to be used by DCs.…”
Section: Limitationsmentioning
confidence: 99%